Prevention Risk Behavior of HIV/AIDS in Senior High School Student - Puspita, Ferya; Yusriani, Yusriani; Idris, Fairus Prihatin (PT.Mantaya Idea Batara, 2024)
World Health Organization (WHO) data are 680.000 people died by HIV in 2020. Based on data, 99.000 are chidren under 15 years ages and 580.000 are adults over 15 years. The number of HIV case in Gowa district from years 2021 to on November 2023 grow up. In years 2021 number of HIV cases are 55 peoples. In years 2022 number os HIV cases are 72 peoples. Number of HIV cases in years 2023 until on November is found the number is 136 peoples. The aim of this research is to analyze the prevention of HIV/AIDS risk behavior among students at SMA Senior 1 Gowa.. Quantitative research. The number of sample are 194 respondents by purposive sampling. Data source from sekunder data in 2024. The results of analysis described gender toward risky behavior (p value 0.290). economy status toward risky behavior (p value 0.316). attitude toward risky behavior (p value 0.092). cultural toward risky behavior (p value 0.081). media toward risky behavior (p value 0.000). obedience religious toward risky behavior (p value 0.000). knowledge towar risky behavior (p value 0.000). Conclussion, on no effectedon gender, economy status, attitude, and culture. Nonetheless, effected on media, obedience religious and knowledge.